Empowerment of the Urban Poor in Improving Food Security (Case Study: Development of Juma Cindai Garden in Cinta Damai Village) - Sitepu, Nelly Fitriani; Bengkel, Bengkel; Ridho, Hatta; Irmayani, Tengku; Kusmanto, Heri (East Asian Journal of Multidisciplinary Research, 2024)
This research investigates the role of community empowerment in enhancing food security within urban areas, focusing on the development of the Juma Cindai Agroeducation Garden in Cinta Damai Village, Medan, Indonesia. Utilizing qualitative methodologies, data were collected through interviews, observations, and documentation. The findings highlight that unifying scattered farmer groups into the Juma Cindai Agroeducation Group significantly improved the efficiency and effectiveness of empowerment programs. Regular community discussions and FGDs facilitated the planning and implementation of relevant activities, such as hydroponics training. Positive community responses and active participation indicated a successful empowerment initiative. Intensive monitoring and evaluation ensured the program's alignment with its objectives, fostering technical skill development and social mindset shifts toward sustainable agriculture. The study concludes that structured community empowerment through urban agriculture can effectively enhance food security, economic independence, and community resilience against urbanization's impacts.